Extensive Introgression among Ancestral mtDNA Lineages: Phylogenetic Relationships of the Utaka within the Lake Malawi Cichlid Flock. (10th May 2012) - Anseeuw, Dieter; Nevado, Bruno; Busselen, Paul; Snoeks, Jos; Verheyen, Erik
Abstract : We present a comprehensive phylogenetic analysis of the Utaka, an informal taxonomic group of cichlid species from Lake Malawi. We analyse both nuclear and mtDNA data from five Utaka species representing two ( Copadichromis and Mchenga ) of the three genera within Utaka. Within three of the five analysed species we find two very divergent mtDNA lineages. These lineages are widespread and occur sympatrically in conspecific individuals in different areas throughout the lake. In a broader taxonomic context including representatives of the main groups within the Lake Malawi cichlid fauna, we find that one of these lineages clusters within the non-Mbuna mtDNA clade, while the other forms a separate clade stemming from the base of the Malawian cichlid radiation. This second mtDNA lineage was only found in Utaka individuals, mostly within Copadichromis sp. "virginalis kajose" specimens. The nuclear genes analysed, on the other hand, did not show traces of divergence within each species. We suggest that the discrepancy between the mtDNA and the nuclear DNA signatures is best explained by a past hybridisation event by which the mtDNA of another species introgressed into the ancestral Copadichromis sp. "virginalis kajose" gene pool.